Pemanfaatan Buku KIA Upaya Deteksi Dini Tumbuh Kembang Anak di Kecamatan Panca Lautang Kabupaten Sidrap - Hamdiyah; Fitriani; Mardiana Ahmad; Rusdiana (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Community service activities are activities carried out in the stunting locus area in Sidrap Regency, which are the service activities and responsibilities of ITKES Muhammadiyah Sidrap lecturers and students. The purpose of this community service activity is to improve the quality of maternal and child health, it is necessary to implement the use of the MCH handbook in the context of stunting prevention which is carried out at the Cendana Village Office, Sidenreng Rappang Regency. The method of implementing this activity is a site survey, activity plan, activity implementation and activity evaluation. The results of this community service activity in the health sector show the enthusiasm, motivation and enthusiasm of the community in participating in this activity. This PKM activity was carried out at the Cendrana Village Office which was attended by government officials, pregnant women, cadres, parents, community leaders in Cendana village. This activity was carried out in conjunction with free medical check-ups conducted by students, then socialization was carried out on the use of MCH books by lecturers. The consistency of the academic community in carrying out community service activities in the health sector needs to be maintained and even improved in order to support the tri dharma of higher education.